Influence of humic acid on the immobilization of U(VI) by montmorillonite in simulated environmental conditions. Issue 5 (24th March 2018) - Xin, Yu; Wang, Jiaquan; Li, Yuying; Asiri, Abdullah M.; Marwani, Hadi M.; Hu, Shuheng; Wang, Gan; Xu, Zimu
ABSTRACT: Effect of solution conditions (such as contact time, solution pH, ionic strength, reaction temperature, solid-liquid ratio and humic acid (HA)) on U(VI) immobilization on montmorillonite from Huangshan, China in environment was investigated by batch technique. U(VI) adsorption on montmorillonite is fairly affected by the solution pH and the ionic strength. Thermodynamic parameters (ΔH°, ΔS°, and ΔG°) suggest that U(VI) adsorption on montmorillonite shows a spontaneous and endothermic process. The coexisted HA in solution could promote the U(VI) adsorption on montmorillonite. Notably, Huangshan montmorillonite has the potential in enrichment and solidification of U(VI) ions under environmental conditions.